2007
DOI: 10.1086/520587
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Hemorrhagic Fever: Evaluation of Passive Immunotherapy in Nonhuman Primates

Abstract: The survival of 7 of 8 patients with Ebola virus (EBOV) infection after transfusions of convalescent-phase blood during a 1995 outbreak of EBOV infection is frequently cited as evidence that passive immunotherapy is a viable treatment option. To test whether whole-blood transfusions were more efficacious than passively administered immunoglobulins or monoclonal antibodies, we transfused convalescent-phase blood from EBOV-immune monkeys into naive animals shortly after challenge with EBOV. Although passively ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 13 publications
0
72
0
3
Order By: Relevance
“…However, the authors involved with the study concluded that a number of factors other than administration of convalescent blood could have contributed to the high survival observed among these patients. Two preclinical studies in NHPs have attempted to replicate this study with the use of either convalescent NHP whole blood 121 or convalescent NHP serum 122 (TABLE 1). In an initial study, four rhesus monkeys were treated with homologous convalescent whole blood from rhesus macaque donors immediately after EBOV (Kikwit strain) challenge and again on day 3 or 4 after exposure 121 .…”
Section: Box 4 | Screening Systems For Drug Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors involved with the study concluded that a number of factors other than administration of convalescent blood could have contributed to the high survival observed among these patients. Two preclinical studies in NHPs have attempted to replicate this study with the use of either convalescent NHP whole blood 121 or convalescent NHP serum 122 (TABLE 1). In an initial study, four rhesus monkeys were treated with homologous convalescent whole blood from rhesus macaque donors immediately after EBOV (Kikwit strain) challenge and again on day 3 or 4 after exposure 121 .…”
Section: Box 4 | Screening Systems For Drug Developmentmentioning
confidence: 99%
“…Two preclinical studies in NHPs have attempted to replicate this study with the use of either convalescent NHP whole blood 121 or convalescent NHP serum 122 (TABLE 1). In an initial study, four rhesus monkeys were treated with homologous convalescent whole blood from rhesus macaque donors immediately after EBOV (Kikwit strain) challenge and again on day 3 or 4 after exposure 121 . Serum levels of anti-EBOV antibodies were comparable to levels associated with protective vaccination; however, all treated animals succumbed to the infection with no delay in death versus controls 121 .…”
Section: Box 4 | Screening Systems For Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…26). Similarly, neutralizing polyclonal antibody also failed to protect NHPs (27). However, protection with polyclonal antibody against another filovirus, Marburg, has recently been reported (John Dye et al; Chemical and Biological Defense Science and Technology Conference, 15-19 November 2010 in Orlando, FL), suggesting that, with the right specificity, protection against EBOV should be achievable.…”
Section: Discussionmentioning
confidence: 98%
“…Passive transfer of serum collected from survivors of Junin virus or Lassa virus has proven effective provided treatments are initiated soon after infection (4)(5)(6). However, antibody passive transfer experiments have been largely unsuccessful in treating filovirus infections (7). During a 1995 outbreak of EBOV in Kikwit, Democratic Republic of the Congo, seven of eight patients who exhibited symptoms and detectable EBOV antigen in their blood survived disease after treatment with whole blood from convalescent EBOV survivors (8).…”
mentioning
confidence: 99%